Natural implementation with semi-responsible agents in pure exchange economies - Michele Lombardi; Naoki Yoshihara (University of Massachusetts, Department of Economics, 2017)
We study Nash implementation by natural price-quantity mechanisms in pure exchange economies when agents have intrinsic preferences for responsibility. An agent has an intrinsic preference for responsibility if she cares about truth-telling that is in line with the goal of the mechanism designer besides her material well-being. A semi-responsible agent is an agent who, given what her opponents do, acts in an irresponsible manner when a responsible behavior poses obstacles to her material well-being. The class of efficient allocation rules that are Nash implementable is identified provided that there is at least one agent who is semi-responsible. The Walrasian rule is shown to belong to that class.
Keywords: C72; D71; 330; Nash equilibrium; exchange economies; intrinsic preferences for responsibility; boundary problem; price-quantity mechanism